New insights into microRNA in dermatological diseases - Xu, Mengting; Yan, Jiadong; Wang, Xin; Zhang, Yue; Yang, Shengju (Frontiers in Medicine, 2025)
MicroRNAs (miRs) are a class of non-coding RNA molecules that regulate gene expression post-transcriptionally. MiRs, as translational repression and/or degradation of target messenger RNAs, are critical regulators of various physiological processes, including cell proliferation, differentiation, death, and immune responses. Currently, miRs are being investigated as potential biomarkers and therapeutic targets for a range of diseases. In recent years, miRs have been reported to be implicated in several pathophysiological processes of dermatological diseases including psoriasis, skin wound, diabetic skin wound, burn, systemic sclerosis, skin tumors (melanoma, squamous cell carcinoma and basal cell carcinoma), recessive dystrophic epidermolysis bullosa, and systemic lupus erythematosus. Mechanistically, the regulation of oxidative stress, inflammation, apoptosis, and angiogenesis may account for the distinct roles of miRs in the skin. A deeper understanding of different miRs and their related regulatory targets is essential for elucidating the pathophysiology of numerous skin diseases. This review briefly summarizes roles and potential applications of miRs within the skin. The combination of miRs with novel materials or compounds may offer innovative approaches for the treatment of skin diseases. However, further research is necessary to facilitate the translation into clinical applications for dermatological diseases.